Sobol' sensitivity analysis of the Holocene Peat Model: What drives carbon accumulation in peatlands?. Issue 1 (27th February 2013) - Quillet, Anne; Garneau, Michelle; Frolking, Steve
Abstract : [1] Understanding the development of northern peatlands and their carbon accumulation dynamics is crucial in order to confidently integrate northern peatlands into global carbon cycle models. To achieve this, northern peatland models are becoming increasingly complex and now include feedback processes between peat depth, decomposition, hydrology, and vegetation composition and productivity. Here we present results from a global sensitivity analysis performed to assess the behavior and parameter interaction of a peatland simulation model. A series of simulations of the Holocene Peat Model were performed with different parameter combinations in order to assess the role of parameter interactions on the simulated total carbon mass after 5000 years of peatland development. The impact of parameter uncertainty on the simulation results is highlighted, as is the importance of multiple parameter interactions. The model sensitivity indicates that peat physical properties play an important role in peat accumulation; these parameters are poorly constrained by observations and should be a focus of future research. Furthermore, the results show that autogenic processes are able to produce a wide range of peatland development behaviors independently of any external environmental changes. Key Points: Peat physical properties are key processes and should be further investigated Autogenic processes can lead to various peatland development patterns Lawn and hummock Sphagnum PFTs are able to modify carbon accumulation dynamics